Peranan PPAT dalam Pendaftaran Hak Tanggungan Secara Elektronik di Kota Sungai Penuh - Setiawan J, Pujha; Fendri, Azmi; Syofiarti, Syofiarti (Universitas Ekasakti, 2023)
PPAT is a public official authorized to draw up Deeds for Granting Mortgage Rights (APHT), in which the deed will be used as basic evidence for registration of Mortgage Rights at the Land Office and PPAT is required to submit APHT and supporting documents to the Land Office within 7 days after the deed is signed. In Article 14 of the Electronic Mortgage Service Regulations, it has also been limited to the 7th day, if it is not carried out then the PPAT mortgage registration document is automatically uploaded, it is considered giving approval by the system. The presence of Electronic Mortgage Registration has not run smoothly and has resulted in APHT and supporting documents submitted by the PPAT in the Sungai Full City area to the Land Office past the applicable regulatory deadline. The results of the study found that: 1. The role of the PPAT is to check Certificate, Making Deed of Granting Mortgage Rights (APHT), Power of Attorney for Imposing Mortgage Rights (SKMHT), and submitting Deeds for Granting Mortgage Rights and supporting documents to Creditors (Banks) to continue registration to the Land Office by Creditors (Banks), but with a lack of understanding and the knowledge of the PPAT in SungaiFull City regarding the registration of Mortgage through electronic system services, the role of the PPAT in SungaiFull City is still not in accordance with Ministerial Regulation Number 5 of 2020 concerning Electronically Integrated Mortgage Services. 2. PPAT Constraints in Registering Mortgage Rights Electronically in Sungai Full City, namely: There is still a lack of inspection, Network Disruption, collateral object certificates have not been validated and problems found, there are legal violations against PPATs who do not comply with the time limit provisions in submitting APHT and supporting documents to the Land Office and abusing authority by carrying out creditor user account obligations.